2008
DOI: 10.1186/1748-717x-3-4
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-modulated radiotherapy of nasopharyngeal carcinoma: a comparative treatment planning study of photons and protons

Abstract: Background: The aim of this treatment planning study was to investigate the potential advantages of intensity-modulated (IM) proton therapy (IMPT) compared with IM photon therapy (IMRT) in nasopharyngeal carcinoma (NPC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 43 publications
6
80
2
Order By: Relevance
“…In one study [12], dose constraints were defined only for critical neural structures, whereas in the other two studies dose constraints for several other OARs, including the parotid glands, were taken into account. In two studies [12,13], target dose coverage and dose conformity were significantly better using protons, whereas the target dose could be escalated without exceeding the tolerance dose of critical structures [12]. In all studies, the dose to all OARs could be markedly lower (Table 2).…”
Section: Nasopharyngeal Cancermentioning
confidence: 95%
See 3 more Smart Citations
“…In one study [12], dose constraints were defined only for critical neural structures, whereas in the other two studies dose constraints for several other OARs, including the parotid glands, were taken into account. In two studies [12,13], target dose coverage and dose conformity were significantly better using protons, whereas the target dose could be escalated without exceeding the tolerance dose of critical structures [12]. In all studies, the dose to all OARs could be markedly lower (Table 2).…”
Section: Nasopharyngeal Cancermentioning
confidence: 95%
“…Third, most authors only presented average results for all cases [9,13,14,16,18]. It should be noted that the benefit of a new technique in terms of dose distributions in targets and OARs will depend on a number of factors, such as the volume and shape of the target, the position of the target reference to OARs, and the amount of overlap between the PTV and a given OAR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20] For oropharyngeal cancer and nasopharyngeal cancer, the treatment target does not include the brain, oral cavity, submandibular gland, or esophagus. Compared to IMRT, IMPT spares substantial dose to these regions [23] and preliminary results were very encouraging for using this technique. [22] The result of a recent study showed that the percentage of oropharyngeal cancer patients requiring nasogastric tube feeding during concurrent chemoradiotherapy (CCRT) was significantly reduced from 46% by IMRT to 19% by IMPT.…”
Section: Head and Neck Cancers Including Nasopharyngeal Carcinomamentioning
confidence: 94%